From The Fish Middens to the Herring:Medieval and Post-Medieval Fishing in the Northern Isles of Scotland - Harland, Jennifer (2016)
The heyday of Viking Age and medieval fishing in the Northern Isles of Scotland can be traced in the huge deposits of fish bones that appear circa AD 1000. This "fish event horizon" is a phenomenon clearly recognised in the British Isles and linked to numerous factors, including the growing commercialisation of sea fishing in the North Sea and North Atlantic region. However, a few hundred years after the fish midden first appear, fishing in the Northern Isles took a dramatic downturn. Small-scale, subsistence fishing in relatively safe coastal waters became the norm. Early modern writers deplored the state of fishing in the islands in the late 18th century, while repeated attempts to develop commercial fisheries floundered due to lack of knowledge and investment. This paper discusses the archaeological evidence for the period between the 15th to the 19th centuries. Using estimates of fish sizes, species abundance and historical sources, it reconstructs fishing methods and likely fishing grounds, and asks why there was such a striking decline in fishing fortunes in the Northern Isles. The curious absence of herring bones from the archaeological record will also be discussed, a particularly relevant and perplexing question given that the herring industry became so important to the Northern Isles in recent centuries.